The toy [videorecording (DVD)] - Donner, Richard; Pryor, Richard, 1940-2005; Gleason, Jackie, 1916-1987; Chase, Annazette (Columbia Tristar Home Entertainment, 2001)
Gleason is U.S. Bates, a megalomaniac millionaire who owns most of south central Louisiana. Pryor is Jack Brown, a former journalist who has worked his way down the vocational ladder to the position of janitor in Bates' department store. Bates' son, Eric, selects an elaborate toy--Jack Brown--and the relationship teaches Eric more about life than fun and games.